Keyword-Based Model of Teaching English for Adult Learners - Susi Ekalestari; Sri Wulan; Dewi Nurmala; Nurhasanah Nurhasanah; Tristi Ananda (Budapest International Research and Critics University, 2022)
This study discusses the keyword-based model in learning English to for adult learners who in fact have little free time due to various activities but require the ability to communicate in English. Researchers are triggered to make this model because of their weakness in English, so they often have problems communicating with foreign partners. The research method adopted in this study is a qualitative method with descriptive analysis.